Extending the Shelf-Life of Meat and Dairy Products via PET-Modified Packaging Activated With the Antimicrobial Peptide MTP1 - Gogliettino, Marta; Balestrieri, Marco; Ambrosio, Rosa Luisa; Anastasio, Aniello; Smaldone, Giorgio; Proroga, Yolande T. R.; Moretta, Rosalba; Rea, Ilaria; De Stefano, Luca; Agrillo, Bruna; Palmieri, Gianna (Frontiers in Microbiology, 2020)
Fresh products are characterized by reduced shelf-life because they are an excellent growth medium for a lot of microorganisms. Therefore, the microbial spoilage causing significant food supply losses has become an enormous economic and ethical problem worldwide. The antimicrobial packaging is offering a viable solution to tackle this economic and safety issue by extending the shelf-life and improving the quality and safety of fresh products. The goal of this study was to investigate the effects of a food contact surface of polyethylene terephthalate (PET) functionalized with the previously characterized antimicrobial peptide MTP1, in reducing the microbial population related to spoilage and in providing the shelf-life stability of different types of fresh foods such as ricotta cheese and meat. Modified polymers were characterized concerning the procedure of plasma-activation by water contact angle measurements and ATR-FTIR. Results showed that the MTP1-PETs provided a strong antimicrobial effect for spoilage microorganisms with no cytotoxicity on a human colon cancer cell line. Finally, the activated polymers revealed high storage stability and good reusability. This study provided valuable information to develop alternative antimicrobial packaging for enhancing and extending the microbial quality and safety of perishable foods during storage.